Peran Business Process Excellence dalam Keselarasan Proses Bisnis untuk Meningkatkan Kinerja Perusahaan PT Semen Indonesia (Persero) Tbk - Maritza, Talitha Ayu; Sonja Andarini (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research explains the role of Business Process Excellence (BPE) in creating alignment of business processes at PT Semen Indonesia (Persero) Tbk to improve company performance. BPE functions as the primary driver to ensure that all processes run as planned, are well-coordinated, and comply with established guidelines. Through a systematic and structured approach, BPE helps enhance efficiency, inter-departmental coordination, and standardization of business processes. With the implementation of BPE, PT Semen Indonesia successfully reduces operational errors, improves product quality, and achieves better performance. Despite facing challenges in employee and management adaptation to changes, full support from upper management and active involvement of employees help ensure the successful implementation of BPE. This research provides practical guidance for other companies interested in implementing BPE to enhance the alignment and efficiency of their business processes.